Self‐rated health scores predict mortality among people with type 2 diabetes differently across three different country groupings: findings from the ADVANCE and ADVANCE‐ON trials - Hua, X.; Lung, T. W. C.; Woodward, M.; Salomon, J. A.; Hamet, P.; Harrap, S. B.; Mancia, G.; Poulter, N.; Chalmers, J.; Clarke, P. M. (Diabetic medicine, 2020)
Aims To explore whether there is a different strength of association between self‐rated health and all‐cause mortality in people with type 2 diabetes across three country groupings: nine countries grouped together as 'established market economies'; Asia; and Eastern Europe. Methods The ADVANCE trial and its post‐trial follow‐up were used in this study, which included 11 140 people with type 2 diabetes from 20 countries, with a median follow‐up of 9.9 years. Self‐rated health was reported on a 0–100 visual analogue scale. Cox proportional hazard models were fitted to estimate the relationship between the visual analogue scale score and all‐cause mortality, controlling for a range of demographic and clinical risk factors. Interaction terms were used to assess whether the association between the visual analogue scale score and mortality varied across country groupings. Results The visual analogue scale score had different strengths of association with mortality in the three country groupings. A 10‐point increase in visual analogue scale score was associated with a 15% (95% CI 12–18) lower mortality hazard in the established market economies, a 25% (95% CI 21–28) lower hazard in Asia, and an 8% (95% CI 3–13) lower hazard in Eastern Europe. Conclusions Self‐rated health appears to predict 10‐year all‐cause mortality for people with type 2 diabetes worldwide, but this relationship varies across groups of countries. What's new? Self‐rated health is an independent predictor of mortality in people with diabetes. The visual analogue scale (VAS) score has a stronger association with mortality in Asia and a weaker association in Eastern Europe than in the 'established market economies' included in our study among people with type 2 diabetes. People with type 2 diabetes in different countries reporting the same VAS score can face different mortality risks. The VAS score can be a useful global health measure in clinical practice for people with type 2 diabetes, but adjustment would be required before it can be directly compared across countries and regions.